ERdj3, a Stress-inducible Endoplasmic Reticulum DnaJ Homologue, Serves as a CoFactor for BiP's Interactions with Unfolded Substrates - Shen, Ying (The American Society for Cell Biology, 2005)
We recently identified ERdj3 as a component of unassembled immunoglobulin (Ig) heavy chain:BiP complexes. ERdj3 also associates with a number of other protein substrates, including unfolded light chains, a nonsecreted Ig light chain mutant, and the VSV-G ts045 mutant at the nonpermissive temperature. We produced an ERdj3 mutant that was unable to stimulate BiP's ATPase activity in vitro or to bind BiP in vivo. This mutant retained the ability to interact with unfolded protein substrates, suggesting that ERdj3 binds directly to proteins instead of via interactions with BiP. BiP remained bound to unfolded light chains longer than ERdj3, which interacted with unfolded light chains initially, but quickly disassociated before protein folding was completed. This suggests that ERdj3 may bind first to substrates and serve to inhibit protein aggregation until BiP joins the complex, whereas BiP remains bound until folding is complete. Moreover, our findings support a model where interactions with BiP help trigger the release of ERdj3 from the substrate:BiP complex.